Structural inequities in the global supply of personal protective equipment. (15th July 2020) - Garber, Kent; Ajiko, Mary Margaret; Gualtero-Trujillo, Sandra M; Martinez-Vernaza, Samuel; Chichom-Mefire, Alain
Abstract : Low and middle income countries are priced out and facing severe shortages